Band Edge Emission Improvement by Energy Transfer in Hybrid Ⅲ-Nitride/Organic Semiconductor Nanostructure - 蒋府龙 刘亚莹 李扬扬 陈鹏 刘斌 谢自力 修向前 华雪梅 韩平 施毅 张荣 郑有炓 (Chinese physics letters, 2016)
GaN nanorods are fabricated using inductively coupled plasma etching with Ni nano-island masks. The poly [2- methoxy-5-（2-ethyl）hexoxy-l,4-phenylenevinylene] （MEH-PPV）/GaN-nanorod hybrid structure is fabricated by depositing the MEH-PPV film on the GaN nanorods by using the spin-coating process. In the hybrid structure, the spatial separation is minimized to achieve high-emciency non-radiative resonant energy transfer. Optical properties of a novel device consisting of MEH-PPV/GaN-nanorod hybrid structure is studied by analyzing photoluminescenee （PL） spectra. Compared with the pure GaN nanorods, the PL intensity of the band edge emission of GaN in the MEH-PPV/GaN-nanorods is enhanced as much as three times, and the intensity of the yellow band is suppressed slightly. The obtained results are analyzed by energy transfer between the GaN nanorods and the MEH-PPV. An energy transfer model is proposed to explain the phenomenon.